THE USE OF SHEAR GRADIENT VORTICITY IN TROPICAL CYCLONE HEAVY PRECIPITATION PREDICTION： A HIGH-RESOLUTION NUMERICAL CASE STUDY - 汤杰 袁慧玲 王元 费建芳 (Journal of Tropical Meteorology, 2012)
This study introduces a new dynamical quantity, shear gradient vorticity （SGV）, which is defined as vertical wind shear multiplying the horizontal component of vorticity gradient, aiming to diagnose heavy precipitation induced by some strong convective weather systems. The vorticity gradient component can be used to study the collision or merging process between different vortexes or the deformation of a vortex with a sharp vorticity gradient. Vertical wind shear, another contributed component of SGV, always represents the environmental dynamical factor in meteorology. By the combined effect of the two components, overall, SGV can represent the interaction between the environmental wind shear and the evolution of vortexes with a large vorticity gradient. Other traditional vorticity-like dynamical quantities （such as helicity） have the limitation in the diagnosis of the convection, since they do not consider the vorticity gradient. From this perspective, SGV has the potential to diagnose some strong convective weather processes, such as Extratropical Transition （ET） of tropical cyclones and the evolution of multicell storms. The forecast performance of SGV for the numerical ET case of Typhoon Toraji （0108） has been evaluated. Compared with helicity, SGV has shown a greater advantage to forecast the distribution of heavy precipitation more accurately, especially in the frontal zone.